An experimental study of the structural capacity of composite beam (concrete cast I-beam) - Iskandar, Abdul Halim (2017)
Composite beam is type of system that combines the advantages of steel structure and concrete structure to form better building structures for future development. Nowadays, composite beam has been extremely used for built such a mega structures such as bridge and dam. Composite beam contain steel, cement, aggregates, and blend with water. This mixtures is varies on what to build and for what purpose. Concrete is a structure that can be formed into any shape which is good in compression resistance, however weak in tension resistance. The main objectives of this study is to determine ultimate load, deflection of composite beam and stress-strain curve under beam test. The four point load test, using Magnus Frame Machines will be conducted to find ultimate load and the deflection of the composite beam. Samples will be prepared accordingly, and the beam test will be conducted respectively following the sequences in order to come out the best results and achieve the objectives set. Three sample composite beam will be provided for the beam test, in which varies with the location of connector for each composite beam. All the samples of the composite beam are tested at Fakulti Kejuruteraan Awam dan Sumber Alam, Heavy Structure Laboratory, University Malaysia as well as the compressive test which to determine the concrete strength. The finding of this study shows that objectives have been achieved. The results that have been obtained shows that, the ultimate load that composite beam size 0.15m x 0.3m x 2m with I-beam of size 127 x 76 x 8 can sustained is 179.58kN. On the other hand, the maximum deflection for the same beam size can be up to 15.8mm. Based on the previous study, the value obtained for maximum load and deflection is in the range of composite beam capacity and the stress-strain curve for steel and concrete material follows the typical pattern of curve. The pattern for both material was about the same. The both material strain increase directly proportional to the stress until it reached maximum material strain. This indicate the both material of composite beam begin to fail. Then, the both material strain developing necking which shows the decreasing of both strain value, while the stress remained the same throughout the stage. Lastly, with increasing of load and stress, develop a crack and failed to the composite beam and shows that, the negative value of both strain.